Accounting Conservatism in Indonesian Banks: Evidence from Loan Loss Provisions - Agung Nurmansyah; Purwono Purwono; Muhammad Ahmad Baballe (InFestasi, 2026)
The study attempts to investigate the relationship between the recent concepts of prudence in banking literature on the provisioning behaviour in Indonesian banks. We use a mixed exploratory design, including literature review of recent conservatism research with panel evidence from 6 Indonesian banks for years 2021–2024 and preliminary 2025 data. From the results, it is suggested that recent research has repeatedly shown linking accounting conservatism with early recognition of the loss, veracity in financial reports, plus the practice of loan loss provisioning. A negative relationship between credit growth and discretionary loan loss provisions indicated that discretionary provisioning decreased during credit expansion. Although the relations are non-statistically significant due to very small samples taken, the direction of the coefficient suggests some risk of weakening conditional conservatism in an expansion of credit. This study adds to the literature by linking prudence-related constructs with observed effect of provisioning behaviour of Indonesian banks in the IFRS 9. Results offer early insights into the impact of credit growth dynamics on the conservative reporting behaviour. The study also emphasizes the need for public-facing disclosure of provisioning assumptions and macroeconomic scenarios for regulators, investors, and banking professionals.